Damage control approach and reduced resuscitation of the polytraumatized pediatric patient in the emergency room: Abordaje de control de daños y reanimación reducida de paciente pediátrico politraumatizado en urgencias - Figueroa-Uribe, Augusto Flavio (2021)
Polytrauma in pediatric patients is a frequent event, so its timely approach and management define its prognosis. Polytrauma is defined as the presence of two or more traumatic injuries or a single one that endangers life or there is a risk of serious sequelae; resuscitation is understood as the restoration of vital functions of the patient in the pre-hospital area to the hospital area aimed at avoiding the damage caused by the fatal pentad of trauma (coagulopathy, acidosis, hypothermia, hyperglycemia and hypoxia) for which the Damage control protocol which is referred to all the maneuvers that have the purpose of preserving life, but without carrying out definitive repairs in order to mitigate complications derived from the prolonged state of shock, secondary to a prolonged surgical time that postponed adequate resuscitation, this reduced resuscitation consists of 6 precise indications for its performance, being approached from the TEP (Pediatric Evaluation Triangle) and the MARCHDEF protocol (Massive Bleeding, Airway, Breathing, Circulation, Hypothermia, Neurological Deficit, Glycemia, Pain, Exposure, FAST).